2000
DOI: 10.1163/156854100750112798
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Meloidogyne incognita, M. javanica and M. arenaria using sequence characterised amplified region (SCAR) based PCR assays

Abstract: Three randomly amplified polymorphic DNA (RAPD) markers, OPA-12420, OPB-061200 and OPA-01700, species specific to the root-knot nematode species Meloidogyne arenaria, M. incognita and M. javanica respectively, were identified. After sequencing these RAPD-PCR products, longer primers of 18 to 23 nucleotides were designed to complement the terminal DNA sequences of the DNA fragments. This resulted in three pairs of species specific primers that were used to amplify the sequence characterised amplified regions (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(82 citation statements)
references
References 7 publications
8
64
0
10
Order By: Relevance
“…M. javanica was identified by Fjav/Rjav primer produced 670 bp (Figure 1). Our finding showed accordance with previous studies (Zijlstra et al, 2000;Randig et al, 2002, Devran & Söğüt, 2009. Therefore, molecular results indicated that root-knot nematode species used in this study become pure culture.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…M. javanica was identified by Fjav/Rjav primer produced 670 bp (Figure 1). Our finding showed accordance with previous studies (Zijlstra et al, 2000;Randig et al, 2002, Devran & Söğüt, 2009. Therefore, molecular results indicated that root-knot nematode species used in this study become pure culture.…”
Section: Resultssupporting
confidence: 94%
“…Pure culture isolates of M. incognita and M. javanica were confirmed by PCR analysis using the species-specific primers inc14F/inc14R (Randin et al, 2002) and Fjav/Rjav (Zijlstra et al, 2000). The presence of Mi-1 gene in tested plants was checked by Mi23 marker (Seah et al, 2007).…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Bu primerlerin, pozitif olan örneklerde 420 bp'da bant oluşturdukları saptanmıştır (Şekil 3a). Zijlstra et al (2000), dört farklı M. arenaria popülasyonu kullanarak yaptıkları çalışmada, tüm örneklerde 420 bp spesifik DNA bandını elde etmişlerdir. Benzer diğer bir çalışmada Kök-ur nematodlarının moleküler olarak tek bireyden tanımlanması için teşhis anahtarlarının oluşturulması amacıyla üç farklı M. arenaria popülasyonu kullanılmış ve bu örneklerde 420 bp DNA bandı elde edilmiştir (Adam et al, 2007).…”
Section: Moleküler Tanımlamaunclassified
“…Meloidogyne species were identified according to the morphology of the perineal pattern of the females, and by SCAR-PCR markers (Zijlstra et al 2000).…”
Section: Sampling and Isolation Of Meloidogyne Spp Eggsmentioning
confidence: 99%